APLIKASI METODE TRANSPORTASI DALAM OPTIMASI BIAYA DISTRIBUSI BERAS SEJAHTERA PADA PERUM BULOG SUB-DIVRE SIDOARJO - Azizah, Nuril Lutvi; Suryawinata, Mohammad (Universitas Dr. Soetomo, 2018)
Transportation method is a method used to manage the distribution of sources that provide the same product, to places that require optimally so that the cost of distribution issued is minimal. This method can be used to determine the most effective allocation of goods from a source to a destination at the most possible optimal cost. This research was conducted on Bulog Divre of East Java with Case Study of Bulog Sub-Divre Sidoarjo for several rice distributions located in the district in Sidoarjo. The aims of this research is to determine whether the Transportation Method can provide an efficient solution of costs on the distribution of prosperous rice in the region of Sidoarjo. The method used in this research is VAM (Vogel’s Aprroximation Method) method used to analyze the initial fiscal solution, and enhanced by MODI (Modified Distribution Method) method to analyze the most optimal cost. From the calculation by transportation method, it is found that the optimum cost is lower than the calculation of the company, where the cost obtained by transportation method is Rp.85.186.035,750,- while the cost of the company calculation is Rp.87.209.690,750. Thus the use of transportation methods can save RASKIN distribution costs of Rp.2.023.655,000, -.